THE IMPACT OF INCLUSIVE EDUCATION IMPLEMENTATION ON ELEMENTARY SCHOOL STUDENTS BY THE YOGYAKARTA CITY DISABILITY SERVICES UNIT - Zulfa Jihan Hanifa; Moh Salimi; Sukarno (Jurnal Cakrawala Pendas, 2026)
The execution of inclusive education in Indonesia continues to encounter obstacles, particularly concerning limited human resources, complex bureaucracy and public awareness. This research investigates the effects of inclusive education policy implementation via the Technical Implementation Unit for Disability Services in Education and Resource Center (ULD) of Yogyakarta City, which is a pioneering local institution in Indonesia. Employing a qualitative case study methodology, data were gathered through interviews with key ULD officials, document analysis, and questionnaires distributed to special assistant teachers. The results reveal that the ULD has produced sustained positive effects across various stakeholders. At the community level, heightened public awareness has fostered greater acceptance of children with disabilities and improved access to formal education through affirmative pathways. At the school and teacher levels, the ULD has bolstered institutional capacity by increasing the number of special assistant teachers and enhancing teachers’ competencies through ongoing training. At the student level, inclusive practices have facilitated positive academic, social, and emotional development among students with disabilities. This research adds to the body of literature on inclusive education policy implementation by illustrating the strategic role of local technical institutions in connecting national policy frameworks with inclusive practices at the school level.